Reliability Analysis of 20 KV Electric Power Distribution System. Issue 1 (May 2020) - Nazaruddin; Mahalla; Fauzi; Maimun; Subhan; Abubakar, Said; Aiyub, Sayed
Abstract: The reliability of the distribution system is the ability of a system to supply electrical energy continuously without causing failure to consumers. The reliability of the distribution system can be analyzed based on the SAIDI (System Average Interruption Duration Index), SAIFI (System Average Interruption Frequency Index), and CAIDI (Customer Average Interruption Duration Index) indices. The SAIFI, SAIDI and CAIDI values are determined by simulating using ETAP 12.0.6 software, which is by running reliability assessment analysis. The simulation process was carried out an IEEE 9 bus network distribution system. The simulation results show a SAIFI value of 1.113 frequency/customer.yr, a SAIDI value of 17.306 hours / customer.yr and a CAIDI value of 15, 549 hours / customer interruption. For normal operating conditions, the total demand for loads supplied from secondary substations to the 20 KV distribution network is 12, 955 MW and 5, 234 MVAR, with losses of 8.06%